Semantic web technologies and e-business : toward the integrated virtual organization and business process automation - Salam, A. F., 1966-; Stevens, Jason R., 1976- (Hershey, PA : Idea Group Pub., 2007)
"This book presents research related to the application of semantic Web technologies, including semantic service-oriented architecture, semantic content management, and semantic knowledge sharing in e-business processes. It compiles research from experts around the globe to bring to the forefront the many issues surrounding the application of semantic Web technologies in e-business"--Provided by publisher.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Electronic commerce; Semantic Web; Internet; Business enterprises -- Computer networks